Diaphragm weakness as a cause of breathlessness after anatomically distant surgery. Issue 9 (31st August 2005) - Moore, A J; Moxham, J; Polkey, M I
Abstract : The case histories are presented of two patients in whom breathlessness developed following surgery to an anatomically distant site. Respiratory muscle testing demonstrated diaphragm weakness in both patients.